The Analysis of Use Register for Computer System Based on English For Specific Purpose (ESP) Theories at Vocational High School Al-Huda Sumber Nangka Pamekasan - Siti Mukamilah; Ary Iswahyudi (Universitas Islam Madura, 2018)
English has a more specific coverage, it is known as